GAMBARAN KEPATUHAN DIET DAN DUKUNGAN KELUARGA PADA PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA RAWAT JALAN DI RSU HAJI MEDAN TAHUN 2014 - Erikka Magdalena Panjaitan; Mhd.Arifin Siregar; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The body of human is the site of a variety of metabolic processes to sustain the life. The metabolic process produces the hazardous waste materials that if it was accumulated in the body. The failure of kidney function to maintain the metabolism and balance the liquid and electrolyte is called by the chronic renal failure. The study was conducted by using a descriptive study with a cross sectional design which aimed to know the description of dietary pursuance and family support in chronic renal failure patients who underwent the out patients hemodialysis in RSU Haji Medan. The samples that was taken was all population of chronic renal failure patients were as many as 32 people. In the study, the respondents was a family who understood and regulated the diet of patients. Data that was collected include the identity of the patient, dietary pursuance, and family support. The results of this research shows that the obedient of the chronical renal failure are 19 people and the unobedient of the chronical renal failure are 13 people. Most of the support from the family of chronic renal failure are generally in a good category. The dietary pursuance of chronic renal failure patients which is supported by a good family, the obedient patients are 19 people and the unobedient patiens are 12 people. It was expected to HR RS especially for (doctors and nurses) in order to improve the provision of better education about diet chronic renal failure patients. For families to provide appropriate food diet and to encourage chronic renal failure patients. Keywords: Dietary pursuance, family support, chronic renal failure